Instructional Communication Process in Online Learning (School From Home) during Covid-19 Pandemic - Dea Riyana Wahyuni; Vininda Aulia; Rino Febrianno Boer (JTP - Jurnal Teknologi Pendidikan, 2021)
Indonesia government taking some actions to break the chain of Covid-19 virus such as Study from Home or online learning that allow teachers and students to study online from their home. The existence of online learning rapidly grows due to the pandemic and changes the way the teachers and the students communicate each other during the class. This research aims to see how the process of instructional communication applied by teacher in doing online learning process in the past few months due to the Covid-19 pandemic. The methodology used in doing the research was qualitative and descriptive approach. This research used Post-Positivism as research paradigm. Data collection techniques were deep interview with the teacher and online classroom observation. Referring to the data analysis model about factors to achieve the instructional communication target such as students’ characteristic, teacher’s characteristic, interaction and methods of delivering the messages, physical facility and surrounding environment, the data analysis technique used was qualitative. This research revealed that instructional communication applied in teaching vocational students is verbal and non-verbal communication. In short, there are two points needed to be highlight for the communication between the teacher and the students during online learning process which are teacher character and the variety used of media. The use of media is divided into two sub points which are main media (Google Classroom and Google Meets) and supported media (Power Point, learning material video and Whatsapp group). Teacher used those media in delivery the lessons to the students to support the online learning process.